Analysis of the Influence of Work Culture Transformation and International Standards on Job Satisfaction in the Manufacturing Industry in Bandung - Mei Rani Amalia; Setyowati Subroto (Westscience Press, 2025)
This study investigates the influence of work culture transformation and the implementation of international standards on job satisfaction in the manufacturing industry in Bandung. Utilizing a quantitative approach with 85 respondents, data were gathered through a structured questionnaire employing a 5-point Likert scale. Statistical analysis was conducted using SPSS version 26. Results reveal that both work culture transformation and international standards significantly and positively affect job satisfaction, with international standards having a slightly stronger influence. The findings underscore the synergistic relationship between cultural alignment and operational excellence in fostering a satisfied workforce. These insights offer practical guidance for manufacturing firms aiming to enhance employee satisfaction while maintaining global competitiveness.